2021
DOI: 10.2355/isijinternational.isijint-2020-348
|View full text |Cite
|
Sign up to set email alerts
|

Positive Catalytic Effect and Mechanism of Iron on the Gasification Reactivity of Coke using Thermogravimetry and Density Functional Theory

Abstract: The catalytic gasification characteristics and kinetics of metallurgical coke by iron were investigated by non-isothermal thermogravimetry using volumetric (VM), unreacted core (URCM), and random pore (RPM) models. Density functional theory (DFT) calculations were used to analyse the interaction mechanism of CO 2 on the iron catalyst surface. Carbon conversion curves were shifted to a lower-temperature zone upon iron addition, indicating the strong catalytic effect of iron on carbon gasification. Kinetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Based on the above analysis, the reduction of FeO to Fe in sinter A and the gasification reaction of ICA are jointly the reaction rate limiting link in stage 1 of the reaction. The activation energy of the gasification reaction of ICA is higher, which requires crossing a higher energy barrier than the reduction reaction of sinter A [41][42][43] . Therefore, the activation energy required for the joint occurrence of the two reactions depends on the activation energy of the gasification reaction of ICA, and the joint occurrence of the two reactions requires more energy than that of pure sinter A.…”
Section: Kinetic Analysis and Establishment Of Kinetic Modelmentioning
confidence: 99%
“…Based on the above analysis, the reduction of FeO to Fe in sinter A and the gasification reaction of ICA are jointly the reaction rate limiting link in stage 1 of the reaction. The activation energy of the gasification reaction of ICA is higher, which requires crossing a higher energy barrier than the reduction reaction of sinter A [41][42][43] . Therefore, the activation energy required for the joint occurrence of the two reactions depends on the activation energy of the gasification reaction of ICA, and the joint occurrence of the two reactions requires more energy than that of pure sinter A.…”
Section: Kinetic Analysis and Establishment Of Kinetic Modelmentioning
confidence: 99%
“…Furthermore, the catalytic effect of Fe on iron coke gasification was attributed to the fact that Fe reduced the energy required for the decomposition of ketone groups, as shown in Figure 11c. Li et al [ 81 ] further analyzed the interaction mechanism of CO 2 on the Fe catalyst surface using DFT and showed that CO 2 molecules parallel to the crystal surface easily interacted with the Fe surface. Moreover, the surface (0 0 1) of Fe crystal could activate CO 2 molecules and reduce the activation energy of the gasification reaction, which made it an excellent catalyst for coke gasification, as shown in Figure 11d,e.…”
Section: Metallurgical Properties Of Iron Cokementioning
confidence: 99%
“…Bi et al [ 80 ] used an infrared gas analyzer to monitor the composition and content in the tail gas of the iron coke gasification in real time and defined the temperature corresponding to a volume fraction of CO in the tail gas of 1% as the initial reaction temperature. Li et al [ 81 ] investigated the effect of iron on the behavior of the coke gasification using a thermogravimetric analyzer, defining the temperature at a carbon conversion of 0.05 as the initial reaction temperature. The results showed that the whole reaction shifted to the low‐temperature zone under the catalytic effect of iron, and the trend increased with the increase of iron content.…”
Section: Metallurgical Properties Of Iron Cokementioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetric analysis has been widely used to measure the loss of mass with temperature and time to determine the kinetic parameters. To ensure that all of the weight loss is caused by the reaction consumption of carbon and CO 2 , the coke samples must be dried for 2 h in N 2 atmosphere at 1073 K. The carbon conversion in coke gasification can be expressed as below where m i (mg) is the initial mass of the sample after drying at 1073 K in N 2 atmosphere, m t (mg) is the mass of the sample at time t , and m f (mg) is the mass of the sample at the end of the reaction. The conversion rate is a function of the rate constant k ( T ) and the mechanism function f ( x ) for heterogeneous solid reactions, as shown in eq where t (s) is the time, T (K) is the temperature, and k ( T ) can be expressed by the famous Arrhenius equation where A (s –1 ) is the pre-exponential factor, which is proportional to the reaction rate.…”
Section: Kinetic Analysismentioning
confidence: 99%